PENGELOLAAN DANA DESA DALAM PEMBANGUNAN INFRASTRUKTUR - Yasir, Ahmad (Cross-Border Journal of Business Management, 2024)
Village Funds originate from the State Revenue and Expenditure Budget (APBN) and are utilized for development and welfare, particularly in rural areas. Village Funds are expected to have a highly positive impact on infrastructure development. However, in reality, many community facilities, such as village roads, cannot yet be considered adequate, which may disrupt daily mobility or traffic flow for the community. Using a qualitative approach, this study employs primary data obtained through direct interviews with informants and secondary data collected from the Mekar Sekuntum village office and the Central Statistics Agency of Sambas Regency. The analysis method involves calculating the effectiveness ratio to measure the level of effectiveness. The results of this study indicate that the management of Village Funds sourced from the APBN is entirely used for village development to achieve national development goals. Village Funds are considered effective when they are utilized in accordance with the objectives of the Village Fund policy itself. Village Funds aim to realize development in villages. Based on research conducted on the effectiveness of Village Fund policies in infrastructure development in Mekar Sekuntum Village, Tebas District, Sambas Regency, the management of Village Funds is declared compliant with the Republic of Indonesia Law Number 6 of 2014 on Villages, Ministry of Home Affairs Regulation Number 113 of 2014 on Village Financial Management, and Sambas Regent Regulation Number 48 of 2018 on Village Financial Management.